2019
DOI: 10.3390/ma12060971
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Carbon Nanotube-Based Polymer Electrode for Long-Term Electrocardiographic Recording

Abstract: The long-term monitoring of electrocardiogram (ECG) is critical for the accurate diagnosis and tracking of cardiovascular diseases (CVDs). However, the commercial Ag/AgCl electrode is not suitable for long-term monitoring due to skin allergies and signal degradation, caused by the conductive gel drying over time. In this paper, a flexible gel-free electrode, composed of a multi-wall carbon nanotube (MWCNT) and polydimethylsiloxane (PDMS), is proposed for long-term wearable ECG monitoring. To achieve uniform di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…Carbon-based materials (such as CNTs [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ], graphene [ 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ] or carbon black [ 68 ]) possess high mechanical strength and good electrical conductivity. To harness their unique properties, CNTs are often dispersed into a polymer matrix to fabricate electrodes.…”
Section: Surface Dry Electrodesmentioning
confidence: 99%
“…Carbon-based materials (such as CNTs [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ], graphene [ 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ] or carbon black [ 68 ]) possess high mechanical strength and good electrical conductivity. To harness their unique properties, CNTs are often dispersed into a polymer matrix to fabricate electrodes.…”
Section: Surface Dry Electrodesmentioning
confidence: 99%
“…What is encouraging from the practical point of view is that repeated washing of such textiles showed only a small decrease of performance of 6% in terms of electrical resistance. Regarding the performance, Chi and co-workers showed that a CNT-based sensor can be used for daily monitoring of ECG signals, outperforming the traditional Ag/AgCl electrodes [ 149 ]. Despite the impressive progress in this area, we are yet to find out how the proposed e-Textiles for ECG measurement perform in the long term.…”
Section: The Opportunities Offered By Wearable Sensors From Cntsmentioning
confidence: 99%
“…An abundance of articles demonstrates how various types of CNTs can be used for ECG acquisition [149][150][151][152][153][154]. Typically, the nanocarbon component is introduced to a flexible polymer matrix, such as polydimethylsiloxane or polyurethane, to make the device convenient to the user and ensure appropriate adhesion to the skin [155,156].…”
Section: Ecgmentioning
confidence: 99%
“…Therefore, wet-or stickytype electrodes are employed for the system 12 . Although such wettype electrodes are appropriate for solving the contact issue, they can cause skin irritation and allergy in patients 13,14 . In addition, it is not appropriate to monitor BP with the robot because, at each measurement, the electrodes need to be replaced or treated.…”
Section: Introductionmentioning
confidence: 99%